Effect of buffer in simulated body fluid on morphology and crystallinity of hydroxyapatite precipitated on 45S5 bioactive glass-derived glass–ceramic scaffolds: comparison of Good's buffer systems and TRIS - Horkavcová, D.; Stříbny, A.; Schuhladen, Katharina; Bezdička, P.; Boccaccini, Aldo R.; Rohanová, D. (Materials Today Chemistry, 2021)
In vitro tests that verify the ability of a material to form bone-like apatite precipitated (HAp) use a solution that imitates the inorganic part of blood plasma, simulated body fluid (SBF). During such tests, it is necessary to maintain a neutral pH, for which purpose the International Standards Organization recommends the TRIS (tris(hydroxymethyl)aminomethane) buffer (ISO 23,317:2014). To do this, TRIS buffer must remain inert, but, as we have previously reported, TRIS interacts with highly bioreactive materials (such as 45S5 Bioglass-derived scaffolds), thereby accelerating scaffold dissolution. In the search for an alternative to TRIS, we have also recently published results for the 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) and 3-(N-morpholino) propanesulfonic acid (MOPS) buffers, which were also unable to maintain a neutral pH in SBF. Thus, we here continue our search for a more suitable Good's buffer by comparing BES (N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid) and TES (2-[(2-hydroxy-1,1-bis(hydroxymethyl) ethyl) amino] ethanesulfonic acid) with TRIS. 45S5-derived glass–ceramic scaffolds were tested under static–dynamic conditions for bone-like apatite formation using SBF + BES and SBF + TES solutions. The pH measurements, leachate analysis [atomic absorption spectrophotometry (AAS) (Ca2+, SiIV), UltraViolet-Visible (UV-VIS) spectrophotometry (PO4)3−], and scaffold analysis [X-Ray powder diffraction analysis (XRD), X-ray fluorescent analysis (XRF), scanning electron microscopy (SEM)/energy dispersive spectroscopy (EDS), Brunauer.Emmett.Teller specific surface area analysis (BET)] all showed that both BES and TES quickly interacted with the tested material. Moreover, the kinetics of the glass–ceramic dissolution affected the crystallinity and morphology of the precipitated HAp. Based on our previous results and the present data, it appears that Good's buffers are not suitable for the in vitro testing of bioactivity of highly bioreactive materials.
CRIS-Team Scopus Importer:2021-08-06
Keywords: BES buffer; Bioactive high porous material; In vitro test; SBF; TES buffer